Analysis of Students' Science Literacy Ability Profiles Viewed on Competency Aspect Indicators in Science Learning Environmental Pollution Material - Dinas iriandana; Raharjo; Achmad Lutfi (Postgraduate, University of Mataram, 2026)
The twenty-first century is marked by rapid transformations driven by advances in science and technology, which significantly influence human competition and global development. In this era, science literacy has become one of the 16 essential skills identified by the World Economic Forum as crucial competencies for students. Science literacy is defined as the ability to apply scientific knowledge, identify questions, and draw conclusions based on evidence to understand natural phenomena and make informed decisions about the impact of human activities on the environment. This study employed a quantitative descriptive research method aimed at analyzing the profile of students’ science literacy skills based on competency indicators in learning environmental pollution material. The research subjects consisted of 64 students from two classes. Data collection was conducted using a test instrument based on OECD science literacy competencies, which included five indicators with a total of ten questions. The findings revealed that the highest average achievement was in identifying questions within scientific investigations, reaching 73.96%. In contrast, the lowest achievement was in transforming data between representations, with 50.45%. Overall, the average score across all indicators was 60.91%, categorized as moderate level.